Preparation and characterization of LaVO 4/TiO 2 nanotubes and their application in photocatalytic degradation of gaseous toluene under visible light - Zou, X.; Li, Xin Yong; Zhao, Q.; Chen, G. (2012)
LaVO 4/TiO 2 nanotubes, which can response for visible light, were prepared by a facile hydrothermal method, and characterized by TEM, XRD and N 2 adsorption-desorption measurements as well as surface photovoltage spectroscopy. The photocatalytic activity of the LaVO 4/TiO 2 nanotubes was evaluated by degradation of gaseous toluene under visible light(?>420 nm) irradiation. The doped LaVO 4 reduced the average crystal size, enhanced specific surface area and shifted the optical absorption edge to the visible region of TiO 2. The photocatalytic activity of LaVO 4/TiO 2 nanotubes was increased by 47% than pure TiO 2 nanotubes.